Constructivist interpretation of society in western sociology - Lashuk, Iryna V. (Journal of the Belarusian State University. Sociology, 2019)
The purpose of this article is to study the main stages of the formation of a constructivist methodology in sociology. The indicated discourse consisted of differences in the conceptualization of the phenomenon of «society» and the characteristics of its (society) cognition. The main concepts of constructivist interpretation of the «society» phenomenon are considered. The origins of these ideas were formed in the framework of phenomenological philosophy, sociology, ethnomethodology. These theories laid the foundation for social constructivism in the person of P. Berger and T. Lukman, who proclaimed the basic principle of sociological knowledge: «Society exists in both objective and subjective reality». The focus of attention is further focused on the socio-analysis of P. Bourdieu, who seeks to dissociate himself from the structuralist and phenomenological approaches to the study of social reality and introduces the concept of «agent» as opposed to subject and individual.